Modeling the Health Economic Burden of Hepatitis C Virus Infection in Turkey: Cost-Effectiveness of Targeted Screening - Çekin, Ayhan Hilmi; Güner, Rahmet; İnkaya, Ahmet Çağkan and Oğuz, Dilek and Özdemir, Oktay and Tabak, Ömer Fehmi (Turkish Journal of Gastroenterology, 2023)
Background/Aims: In 2016, World Health Organization introduced global goals to eliminate hepatitis C virus by 2030. The aim of this study is to analyze the epidemiologic and economic burden of hepatitis C virus in Turkey and compare current practice (regular care) with a hypothetical active screening and treatment approach (active scenario). Materials and Methods: A Markov model was used to analyze and compare regular care with a scenario developed by experts including the screening and treatment of all acute and chronic hepatitis C virus infections between 2020 and 2050. General and targeted populations were focused. The model reflected the natural history of the disease, and the inputs were based on a literature review and expert opinions. Costs were provided by previous studies and national regulations. Results: The active scenario resulted in higher spending for all groups compared with regular care in the first year. Cumulative costs were equalized in the 8th, 12th, 13th, and 16th year and followed by cost-savings of 49.7 million, 1.1 billion, 288.6 million, and 883.4 million Turkish liras in 20 years for prisoners, refugees, people who inject drugs (PWID), and all population, respectively. In all groups, the mortality was found to be lower with the active scenario. In total, 62.8% and 50.6% of expected deaths with regular care in 5 and 20 years, respectively, were prevented with the active scenario. Conclusions: An active screening and treatment approach for hepatitis C virus infection could be cost-effective for PWID, prisoners, and refugees. Almost two-thirds of deaths in regular care could be prevented in 5 years’ time with this approach.